Forensic Citizens: The Politics of Searching for Disappeared Persons in Mexico - CRUZ-SANTIAGO, ARELY (2017)
In Mexico, thousands of people have disappeared since 2006 due to the so-called ‘War on Drugs’. The government has been unable or unwilling to search and identify many of the disappeared, so families have organised their own searches to locate their loved ones. Through a one year ethnography conducted with relatives searching for their disappeared persons in Mexico, this thesis advances a feminist forensics that not only takes into account attacks inflicted on women, or the lack of female contributions to scientific production, but also looks at Mexico’s disappeared and the contribution their relatives are making to forensic knowledge. The practices, conceptions and struggles of these relatives of disappeared persons reveal the politics of forensic science practice amidst mass atrocities. This alternative forensic practice is one in which citizen’s active participation in spotting, mapping and delineating possible sites where their relatives might be held captive, are transforming the politics and notions of what constitutes evidence and expertise. The politics of forensic expertise is a thread that runs throughout this thesis, and that connects the diverse ways in which disappearance, materiality and subjectivities reconstitute each other to bring forth what I identify as citizen forensics. Thus, by exploring the way in which private citizens are transformed into forensic investigators after the disappearance of a loved one, I contribute a new understanding to the geographical approach to missingness and disappearance. Throughout this thesis I understand disappearance as a fluid technology, at once a political category, created against the backdrop of state violence and pervading insecurity, and also a constantly shifting practice where signifier and signified collapse. The disappeared, in their constant absent/presences and embodiment in maps, GPS, pictures and databases, challenge the distinctions made between the ‘person as such’ and cold bureaucratic technologies such as counting, mapping or case-filing procedures.